True betrayals - Roberts, Nora; Shansky, Rose Anne (Grand Haven, MI : Brilliance Audio, 2008)
Living at a Virginia horse farm with the mother she has never known, Kelsey Byden becomes involved with a high-stakes gambler who raises troubling questions about her mother's past.
Unabridged.
Originally released as sound cassettes in 1995.
Compact discs.
Read by Rose Anne Shansky.
Keywords: Audiobooks